Impact of a digital program on science and technology learning in students with special needs - Portal-Reátegui, Daniel (2025)
This study analyzed how a Digital Learning Program in Science and Technology affects students with special educational needs at IE 2047. A pre-experimental and descriptive study was carried out, evaluating 30 participants using reliable instruments and both descriptive and inferential statistical tools. The results showed a significant increase in post-test scores, a positive relationship between the time the program was used and the improvement in scores, and high reliability of the tools used. These findings suggest that digital technologies can be useful in promoting inclusion and improving learning in challenging educational contexts.